HUMAN-MACAQUE INTERACTIONS ON SON TRA PENINSULA, DA NANG CITY: MANAGEMENT IMPLICATIONS FOR SUSTAINABLE COEXISTENCE - Vinh Thanh, Nguyen; Thang Long, Ha; Bich Thuy, Pham; Tra My, Vu; Huu Vy, Tran; Thi Ngan, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
This study examines the dynamics of human-macaque interactions on the Son Tra Peninsula, focusing on the influence of visitor and primate characteristics. Statistical analysis revealed that interaction distances predominantly ranged between 2 and 3 meters, suggesting a high degree of habituation within the population. A critical disparity was observed between visitor groups, as domestic visitors provisioned macaques with anthropogenic food significantly more frequently than international visitors (χ2 =22.123, p < 0.001). Among the primates, immature macaques were identified as the most active and bold age group, consistently displaying higher interaction intensity than adults or infants (F = 67.75, p < 0.05). Spatial analysis confirmed that Troop 8 and Troop 3 are the most habituated groups, often engaging in high-intensity proximity behaviors. These findings highlight the urgent need for demographic-specific management interventions to mitigate the risks of disease transmission and primate dependency on anthropogenic food.